Honduras : Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The paper reports the progress of the Honduran poverty reduction strategy program, projects, and policy measures. The report provides details on the organization and results of the consultation process, and analyzes the macroeconomic framework for the poverty reduction strategy. An overview of the poverty situation and the performance of the poverty-related economic and social indicators are also discussed. Finally, the adjustment of some poverty reduction strategy program goals and budget is presented. The strategy also proposes a series of policy measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet